Methane emission potential from eutrophic small pond systems - Thant Zin Aung; Cruz, Simon Guerrero; Ekbordin Winijkul; Xue, Wenchao; Loom Nam Khong Pijai (Greater Mekong Subregion) Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Greenhouse gases (GHGs) serve a major role in maintaining our earth{u2019}s climate condition by controlling the balance between incoming and outgoing radiation. However, recent increase in GHGs concentration has caused disruption in the earth{u2019}s energy balance and resulted in various Climate Change events. Among different GHGs{u2019} sources, eutrophicated small ponds (under 0.001 km2) emit significant amounts of methane into the air although they cover small surface area of the earth. However, research on methane emissions from these ponds (both natural and artificial) has not been extensively conducted and the understanding of different methane emission dynamics and mechanisms are still limited. Therefore, this study fulfills the current research gap by studying different methane emissions from eutrophic small ponds under various conditions (i.e., passive and disturbance) together with different water parameters. In this study, natural pond and constructed pond were observed to emit 6.65 (1.54 {u2013} 16.99) mg/m2.hr and 4.21 (0 {u2013} 15.09) mg/m2.hr of total methane flux under passive condition and 7636 (3856 {u2013} 11838) mg/m2.hr and 197 (0 {u2013} 415) mg/m2.hr of total methane flux under disturbance condition respectively. In terms of yearly emissions, the natural pond releases 18.06 kg CH4/year while the constructed pond generate 35.44 kg CH4/year into the atmosphere. Significant differences between passive and disturbed methane fluxes were observed in both natural and artificial ponds, indicating the importance of disturbance to methane emissions. It was also observed that the natural pond tends to be a more serious methane hotspot under disturbance condition due to higher methane flux release derived by thicker sediment layer in natural pond. In addition, this study observed the importance of seasonal/ temporal variations effect (precipitation and atmospheric temperature) on methane emissions and the potential role of different external factors (i.e., pond{u2019}s location, its nearby environment, and activities) on pond{u2019}s resistance against the effect of seasonal/temporal variations.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Greenhouse gases -- Environmental aspects; Methane -- Environmental aspects